Quo natas, Danio?—Recent Progress in Modeling Cancer in Zebrafish - Kirchberger, Stefanie; Sturtzel, Caterina; Pascoal, Susana; Distel, Martin (Frontiers in Oncology, 2017)
Over the last decade zebrafish has proven to be a powerful model in cancer research. Zebrafish form tumors that histologically and genetically resemble human cancers. The live imaging and cost-effective compound screening possible with zebrafish especially complement classic mouse cancer models. Here, we report recent progress in the field, including genetically-engineered zebrafish cancer models, xenotransplantation of human cancer cells into zebrafish, promising approaches towards live investigation of the tumor microenvironment and identification of therapeutic strategies by performing compound screens on zebrafish cancer models. Given the recent advances in genome editing, personalized zebrafish cancer models are now a realistic possibility. In addition, ongoing automation will soon allow high-throughput compound screening using zebrafish cancer models to be part of preclinical precision medicine approaches.